2021
DOI: 10.1186/s13048-021-00905-x
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DLEU1 is overexpressed in premature ovarian failure and sponges miR-146b-5p to increase granulosa cell apoptosis

Abstract: Background miR-146b-5p has been reported to participate in premature ovarian failure (POF) in mice. However, its role in POF patients is unclear. We predicted that miR-146b-5p might interact with lncRNA DLEU1, a crucial player in ovarian cancer. We then explored the interaction between DLEU1 and miR-146b-5p. Methods Expression of DLEU1 and miR-146b-5p in POF and control ovary tissues was determined by RT-qPCR. The subcellular location of DLEU1 in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…However, the role of miRNA in follicular development and atresia and its relationship with premature ovarian failure are still unclear. Many miRNAs are highly conserved, and their expression is tissue-specific, reflecting that they have important physiological functions and play an important role in the regulation of cell growth and development, including cell proliferation, differentiation, and apoptosis [ 13 , 14 ]. The experiment elucidated the effect and underlying mechanism of human umbilical cord mesenchymal stem cells (HUCMSCs) in premature ovarian failure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of miRNA in follicular development and atresia and its relationship with premature ovarian failure are still unclear. Many miRNAs are highly conserved, and their expression is tissue-specific, reflecting that they have important physiological functions and play an important role in the regulation of cell growth and development, including cell proliferation, differentiation, and apoptosis [ 13 , 14 ]. The experiment elucidated the effect and underlying mechanism of human umbilical cord mesenchymal stem cells (HUCMSCs) in premature ovarian failure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have identified an important role for lncRNAs in the regulation of follicle development [ 20 , 21 ]. Studies have identified differential expression of lncRNAs associated with reproductive function by using RNA-seq of OGCs obtained from humans [ 22 ], with most studies focusing on PCOS [ 23 ], endometriosis [ 24 , 25 ], and POF [ 26 , 27 ]. The lncRNAs we identified had fewer exons, shorter ORFs, and shorter transcript lengths compared with those in protein-coding transcripts, and these characteristics were similar to those from porcine OGCs [ 28 ] and human placentas at term [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…One is the interactions between lncRNAs and miRNAs, which may induce ovarian GC apoptosis. For example, Zheng et al found that in POF patients, the lncRNA deleted in lymphocytic leukemia 1 (DLEU1) is upregulated and its overexpression promotes GC apoptosis (Zheng et al, 2021). Zhang et al (Yao et al, 2021).…”
Section: Lncrnas and Pofmentioning
confidence: 99%